Dunkl Hyperbolic Equations - Mejjaoli, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We introduce and study the Dunkl symmetric systems. We prove the well-posedness results for the Cauchy problem for these systems. Eventually we describe the finite speed of it. Next the semi-linear Dunkl-wave equations are also studied.